IDENTIFIKASI POTENSI PERGERAKAN PEJALAN KAKI DI PUSAT PEREKONOMIAN KOTA SINGKAWANG MENGGUNAKAN PEMODELAN URBANO - Agustiah Wulandari; Purnomo, Yudi (Jurnal Arsitektur dan Perencanaan (JUARA), 2024)
Pedestrian movement in the city center can improve the tourist experience of a city with cultural and historical values, such as Singkawang City in West Kalimantan Province. Pedestrian facility planning requires adequate facilities in a good land use and network system. Assessment of walkability using the Urbano analysis tool can provide an assessment of the area's potential regarding connectivity and the quality of pedestrian paths in the economic center area of Singkawang City. The research results show that the study area has a relatively low walk score of 31 out of 100. This figure shows that the Hong Kong Market Area does not generate pedestrian movement. Several variables in Urbano's analysis that can explained are mainly the low intensity and capacity of buildings and distribution patterns of urban facilities that do not support pedestrians. However, it also shows that the daily necessities trading function dominates in generating walking activity in this area, mainly if it includes a banking function.